Inhibitor development upon switching from plasma-derived to recombinant factor VIII in previously untreated patients with severe hemophilia A: the PUP-SWITCH study - Syna Miri; Frits R. Rosendaal; Kaan Kavakli; Peyman Eshghi; Soha Mohammadi Moghaddam; Sara Scardo; Behnaz Habibpanah; Mohsen Elalfy; Susan Halimeh; Gabriella Nicolò; Dilek Gökçebay; Namık Özbek; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: The SIPPET randomized clinical trial showed that in previously untreated patients (PUPs) with severe hemophilia A, treatment with plasma-derived factor (F)VIII (pdFVIII) within the first 50 exposure days (EDs) was associated with a lower cumulative incidence of inhibitors than with recombinant FVIII (rFVIII). Switching to rFVIII beyond 50 EDs with pdFVIII is a treatment often implemented by many centers. The question is whether or not this switch may induce a risk of inhibitor development. Objectives: We investigated if in PUPs with severe hemophilia A switched after 50 EDs from pdFVIII to rFVIII, a novel inhibitor peak appears. Methods: The PUP-SWITCH observational retrospective study was designed to investigate the cumulative incidence of novel inhibitors after switching PUPs to rFVIII after 50 and before 150 EDs. Hemophilia centers that routinely switched PUPs from pdFVIII to rFVIII within this exposure time frame were invited to participate. Patients were followed up for at least 50 EDs after the switch. Results: Ninety-seven patients were evaluated, and 87 were included according to eligibility criteria between 2020 and 2022. Only one of them developed an inhibitor 20 EDs after switching, so the cumulative incidence was 1.15% (95% CI, 0.03%-6.24%). Conclusion: PUP-SWITCH, a study focusing on PUPs undergoing a product class switch from pdFVIII to rFVIII after 50 EDs, showed that switching appears to be safe pertaining to the risk of development of new inhibitors.